Debating Shari‘a in Contemporary Indonesia: Issues, Competing Authorities and the Public Sphere - Fauzi, Muhammad Latif (Tebuireng: Journal of Islamic Studies and Society, 2021)
The transformation of Sharia into a legal code in different Muslim countries is not an easy process. Let alone in Indonesia, this transformation has included dialogues, conflicts and tensions between multiple groups. In the last two decades, along with the growing up of democratic life, this tension has given rise to the emergence of so-called ‘progressive’ and ‘conservative’ movements. Debates among them continue to rage even more intensely. On the other hand, as this article has argued, the development of Islamic family law in Indonesia has demonstrated the increase in the use of modern approaches to Islamic jurisprudence. Nevertheless, the State authority seems to have a decisive power to intervene the content and to determine the result of the debate. Accordingly, I would like to value all these political and legal processes as an inseparable part of the larger process of a public sphere in the Indonesian reformasi era.